Emergence of diversity in a biological evolution model. (March 2015) - Wang, R; Pujos, C
Abstract: The ecological systems comprise a rich diversity of species, but the minimum requirements to maintain a large species diversity on long time scales are in general unknown. Here we propose one neutral evolution competition mechanism which is identified to ensure successful conservation of the biodiversity in ecosystems. Here we show that, this mechanism can lead the system into a quasistable state regardless of the initial conditions. By changing one parameter p which represents the probability of introducing one new species, the system can evolve from homogeneous state, the system contains only one species into heterogeneous state, the system contains diversity of species with number of species equal to the system size. This model is simple enough to be analysed theoretically. The theoretical estimation on abundance distribution and the diversity show the same result of simulation. Furthermore, the lifetime of the species is independent of the system size.